Penerapan Media Flash Card pada Pembelajaran Bahasa Jawa di MI Unggulan Sunan Kudus - Ilfa, Yassir; Kinesti, Rakanita Dyah Ayu (Lembaga Yasin AlSys, 2025)
The low learning outcomes of students in the Javanese Language subject at MI Unggulan Sunan Kudus are attributed to the limited use of instructional media that engage active student participation, thereby necessitating an innovative approach to enhance their comprehension. This study aims to measure the effect of flash card media on student learning outcomes in Javanese Language instruction. Using a qualitative approach with a case study method, data were obtained through observation, interviews, and documentation, and analyzed descriptively. The results show that the use of flash card media has a positive impact on student learning outcomes, as evidenced by a significant increase in scores between the pre-test and post-test results. This medium enhances students’ interest and motivation to learn and facilitates their understanding of the taught material. These findings indicate that flash card media plays an important role as an effective instructional tool in the context of Javanese Language learning at the elementary level. The implication is that teachers are encouraged to integrate this medium as an alternative in the learning process to improve student engagement and comprehension more optimally.